2005
DOI: 10.1902/jop.2005.76.4.558
|View full text |Cite
|
Sign up to set email alerts
|

Risk Indicators of Periodontal Disease in Older Thai Adults

Abstract: Our data suggest that age, gender, education, oral hygiene status, smoking, and diabetes are significantly associated with periodontal disease severity in this study group. Longitudinal studies will establish whether these variables are true risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
175
1
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(195 citation statements)
references
References 26 publications
14
175
1
5
Order By: Relevance
“…Hypertension has been reported to be associated with periodontal disease as latent risks for ischemic heart disease in several studies (7,15,16,20,21) (10,17,18), although we and other investigators (7,15,16,19) …”
Section: T a B L E 2 S P E A R Ma N Co R R E L A T I O N Co E F F Icontrasting
confidence: 56%
See 1 more Smart Citation
“…Hypertension has been reported to be associated with periodontal disease as latent risks for ischemic heart disease in several studies (7,15,16,20,21) (10,17,18), although we and other investigators (7,15,16,19) …”
Section: T a B L E 2 S P E A R Ma N Co R R E L A T I O N Co E F F Icontrasting
confidence: 56%
“…Whether atherogenic factors other than hyperglycemia are linked with periodontal damage, however, is still being debated, and previous studies have reported inconsistent results (6)(7)(8)(9)(10)(13)(14)(15)(16)(17)(18)(19)(20)(21) …”
Section: Periodontitis Has Been Referred To As the Sixth Complicationmentioning
confidence: 99%
“…Various cross-sectional and case-control studies have found a strong association between obesity and periodontal disease (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). It has also been revealed that metabolic syndrome increases the risk of periodontitis, suggesting that people exhibiting several components of metabolic syndrome should be encouraged to undergo regular periodontal examination (7,13,14,(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Uma associação de moderada a forte entre tabagismo e doença periodontal é evidenciada por diversos estudos transversais Floderus-Myrhed, 1983;Albandar et al, 2000;Tomar;Asma, 2000;Bergström, 2003;Hyman;Reid, 2003;Susin et al, 2004a;Natto et al, 2005;Torrungruang et al, 2005;Corraini et al, 2008a) e de caso-controle (Bergström, 1989;Monteiro da Silva et al, 1998;Calsina et al, 2002;Teng et al, 2003).…”
Section: Critérios De Causalidade Entre Tabagismo E Doença Periodontalunclassified
“…Dentre estes estudos, o de Tomar e Asma (2000) destaca-se pela amostra representativa da população dos Estados Unidos, obtida do terceiro "National Health Tomar e Asma, 2000;Albandar et al, 2000;Hyman;Reid, 2003), Brasil (Susin et al, 2004ab;Corraini et al, 2008); Suécia Floderus-Myrhed, 1983;Bergström, 1989;Bergström et al, 2000;Jansson;Lavstedt 2002;Bergström, 2003;Paulander et al, 2004); Arábia Saudita Natto et al, 2005); Tailândia (Teng et al, 2003;Torrungruang et al, 2005;); Alemanha (Gätke et al, 2012;Buchwald et al, 2013); Nova Zelândia (Thomson et al, 2007); Espanha (Calsina et al, 2002) e Canadá (Fisher et al, 2008).…”
Section: Critérios De Causalidade Entre Tabagismo E Doença Periodontalunclassified